1984
DOI: 10.1021/bi00302a005
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR and circular dichroism studies of the B and Z conformations of the self-complementary deoxyhexanucleotide d(m5C-G-C-G-m5C-G): mechanism of the Z-B-coil transitions

Abstract: The double-helical conformations of d(m5-C-G-C-G-m5-C-G) in aqueous solution were studied by circular dichroism and 1H NMR spectroscopy. In 0.1 M NaCl, only the B form is detected whereas the Z form is strongly predominant in 3 M NaCl. In the presence of 2 M NaCl, two resonance signals corresponding to the B and Z duplexes were observed for each proton below 50 degrees C, indicating a slow exchange between B and Z. However, the B-Z exchange becomes intermediate or fast in the 55-80 degrees C temperature interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 36 publications
6
70
1
Order By: Relevance
“…For the base protons the experimental results show that the CH protons of the cytosines are shifted upfield while smaller shifts are measured, on the average, for H8 of guanine (6,7). This clearcut difference between the two types of base is very well given by the calculations.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…For the base protons the experimental results show that the CH protons of the cytosines are shifted upfield while smaller shifts are measured, on the average, for H8 of guanine (6,7). This clearcut difference between the two types of base is very well given by the calculations.…”
Section: Resultssupporting
confidence: 56%
“…Although the degree of purity, in solution, of the Z conformation of the riboses could not be determined, because of the line widths and resonance overlaps (6,7) which prevent the measurement of the coupling constants, we can reasonably suppose that in this case the situation is analogous to that occuring in low salt solution and that the duplexes do not have a perfect regular Z-DNA conformation. This hypothesis is supported by the fact that the values of da obtained for the four different Z-DNA geometries can vary for a sam proton by 0.7 ppm a value which is much larger than the differences experimentaly measured between the four duplexes studied in high salt solutions (see Table 1 and 2 and ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their existence has been definitively proved by X-ray diffraction studies on d(C-G)3 crystals (2). Nuclear magnetic resonance (nmr) (3,4) and Raman spectroscopy (5-9) have also been used to investigate Z DNA. Thamann et al (6) showed that the Raman spectrum of the Z DNA d(C-G), crystal is essentially identical to the high salt solution spectrum of poly(dG-dC).poly(dG-dC).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on d(m5C-G-C-G-m5C-G) [5], d(C-Gm5C-G-T-G) [6] and d(m5C-G)3 [7] have shown that short oligomers are very suitable models to study the B P Z transition in solution by 'H-NMR spectroscopy. Following this work, we examine here the influence of the replacement of two dC and dG residues by dT, dA or d(2aminoA) in alternating d(C-G), oligonucleotides on this structural transition.…”
Section: Poly[d(a-t)] and Poly[d(a-c) D(g-t)] Have Not Been Shown Tmentioning
confidence: 99%